Implementation Of The Levenshtein Algorithm In Zakat Recipient E-Archiving - Sitompul, Nur Wafiqah Azizah; Ali Ikhwan; Muhamad Alda (Jurnal Riset Informatika, 2025)
The rapid advancement of information and communication technology is now increasingly utilized by the public in all sectors of activity, one of which is archival data management. The importance of archival data management today, increases awareness in agencies and organizations by utilizing information technology. Conventional archival data management can result in the possibility of errors that can be caused by several factors, namely, the age of archival data storage, loss of archival data due to work negligence and damage to archival data. Therefore, the existence of a website-based information system that can be used by organizations that can minimize errors in archival data management. The purpose of this study is to design an information system with the implementation of the Levenshtein algorithm on zakat recipient archives at BAZNAS Tapanuli Tengah Regency, where the performance of the Levenshtein algorithm here functions to measure the difference or distance between two strings in order to be efficient in time when searching for stored archival data.